An impossible promise [large type] - Deveraux, Jude; Sheets, Tara, 1973- (Deveraux, Jude. Providence Falls., 2021)
"Liam O'Connor has one purpose in this life--to push the woman he loves into the arms of another man. The Irish rogue unknowingly changed the course of destiny when he fell in love with Cora McLeod over a century ago, and the angels have been trying to restore the balance of fate ever since. Now police officers in Providence Falls, North Carolina, Liam and Cora are partners on a murder investigation. The angels have made it clear Cora must be with Finley Walsh. But Cora is starting to have feelings for Liam. Liam knows this is the last chance to save his soul. But does he love Cora enough to let her go?"--